Sertoli cells tumor in a male canine without cryptorchidism: case report - Gutierrez, Orly Damian (2020)
Testicular neoplasms are a differential diagnosis to consider in the clinical evaluation of dogs that consult for diseases of the genital tract. Its presentation is more frequent in old and cryptorchid dogs. They are considered pathologies of easy diagnosis, although their precise confirmation of the histopathological study. Bilateral orchiectomy is the therapeutic of choice, being curative in most cases. The case of a five-year-old crossbred canine, intact male, not cryptorchid is presented. The owner reports an increase in size in the inguinal region of continuous growth with a month of evolution in the left inguinal region. Ultrasound and histopathology are performed as diagnostic aids and the presence of a Sertoli cell tumour was found.